The Influence of Economic Growth, Human Development Index, and Open Unemployment Rates on Poverty in Sumatra - Tara Fateha Nur Haria; Merri Anitasari (Proceedings of Bengkulu International Conference on Economics, Management, Business, and Accounting, 2023)
The purpose of this study to find out how economic growth, the Human Development Index (HDI), and the open unemployment rate affect poverty in Sumatra. This quantitative research uses panel data for 2012-2021 from 10 provinces in Sumatra sourced from BPS. Panel data regression analysis with the Eviews 13 program was used for the data analysis in this study. The results of the research show that the Human Development Index (HDI) has a negative and significant effect on poverty in Sumatra. Meanwhile, the variables of economic growth and open unemployment have a positive and significant effect on poverty in Sumatra.